91.7k views
2 votes

(1)/(3) {x}^(2) = - 3

The solution to the equation is,,,
A. X = 3
B. No solution
C. X= -3


User Adrena
by
4.3k points

1 Answer

1 vote

Answer:

B

Explanation:

There is no solution to this equation. You get to a point where the equation becomes

x^2 = - 9

That occurs because you multiply both sides of the equation by 3.

But here's the problem.

You are going to have to take the square root of -9. At beginning levels, you don't want to be doing that. So for now, there is no answer.

User Sagar Sakre
by
4.9k points